Orchid‐associated endophytic Bacillus mediates Fusarium suppression and promotes in vitro regeneration of banana plantlets via culture supernatant - Sasongko, Aries Bagus; Purwestri, Yekti Asih; Daryono, Budi Setiadi; Subandiyah, Siti (Universitas Gadjah Mada, 2025)
The application of Fusarium‐antagonistic endophytic bacteria with plant growth‐promoting traits offers an effective method to enhance the success of banana plantlet tissue culture while combating Fusarium wilt disease caused by Fusarium oxysporum f.sp. cubense Tropical Race 4 (FocTR4) (VCG 01213). This study evaluates the endophytic bacterium AP3311, isolated from healthy banana roots in direct association with orchid roots. AP3311 exhibited strong antagonism toward FocTR4, hyphal colonization ability, and multiple growth‐promoting activities, including phosphate solubilization, nitrogen fixation and auxin production. 16S rRNA gene sequencing identified that AP3311 belongs to the genus Bacillus, while metabarcoding analysis revealed that Bacillus species dominate the root microbiomes of both bananas and orchids. The bacterial supernatants stimulated root development and leaf growth in vitro. Metabolomic profiling indicated that antimicrobial compounds, together with plant growth regulators, promoted both root and shoot growth. Overall, the research demonstrates that Bacillus sp. AP3311 and its supernatants are valuable components in banana tissue culture, providing the dual benefits of plant growth promotion and effective disease control.